Serological Surveillance and Diagnostic Performance of Dengue Tests in Brazilian Pediatric Populations (2022–2024) - Ramos-Silva, Valmin; Peçanha, Ariselma Magalhães; Louzada, Bianca Ambrosim; Miranda, Raphael Henrique de Almeida; Miranda, Lidia Costa Barros; Ribeiro, Carla Peruci; Júnior, Pedro Delazare; Bernardes, Gabriela Pinto; Pessini, Natália Marquezini; Monteiro, Sérgio Alexandre Lopes; Vale, Alessandro; Silva, Janine Pereira da (Journal of Advances in Medicine and Medical Research, 2025)
Introduction: Dengue is an endemic arboviral disease in tropical countries, with significant public health impact, especially among pediatric populations. Early diagnosis is crucial for appropriate clinical management and epidemiological control. Serological tests, such as IgM, IgG, and NS1 glycoprotein, are widely used in Brazil, although they present limitations in sensitivity and specificity. Objective: To analyze the use of serological tests in the diagnosis of dengue in Brazilian children between 2022 and 2024, based on data from DATASUS. Method: A retrospective analysis was conducted using secondary data available from the SINAN/DATASUS system between July 13 and 15, 2025. Extracted data referred to probable cases of dengue in Brazilian children, focusing on serological tests (IgM, ELISA, viral isolation, serotyping) recorded across the five regions of Brazil from 2022 to 2024. Results: A total of 2,253,026 dengue cases were reported, with the highest concentration in the Southeast region (1,250,375). IgM serology was positive in 12.4%; ELISA was positive in 26.6%, while viral isolation was confirmed in 0.1% of cases. All four DENV serotypes accounted for 2.9%, with DEN1 being the most frequent. Hospitalizations in the pediatric group were 3.2%. Conclusion: Serological tests remain important tools for dengue diagnosis, especially in settings with limited laboratory infrastructure. Despite advantages such as low cost and rapid results, they face challenges including cross-reactivity and low sensitivity in the early stages of infection. Analysis of national data highlights the importance of combining serological and molecular methods to improve diagnostic accuracy and strengthen the public health response, although clinical epidemiological diagnosis was used in 54.6% of cases to initiate childhood dengue treatment.